Participatory design to support students' web-based inquiry of complex, socio-scientific problems - Oldershaw, Cally; Iolie Nicolaidou; Michael, Georgia; Papadouris, Nicos; Constantinou, Constantinos P.; Kolias, Vassilis; Davaris, Thanassis; Asher, Itay; Tabak, Iris; Redfors, Andreas; Hansson, Lena; Rosberg, Maria; et al. (My University, 2010)
This poster presents five, multilingual, web-based learning environments (LEs) that have been designed using the learning and teaching platform of STOCHASMOS as part of the CoReflect FP7 project. CoReflect brought together eight diverse and multi-disciplinary teams from six European states and one associated country to collaborate for the iterative design, enactment and research of problem-based innovative inquiry LEs. Using STOCHASMOS, each web-based LE was developed by a Local Working Group (LWG), which consisted of researchers, designers, scientists, and practicing teachers to address the research-practice gap. Each LE was piloted in authentic classroom conditions at the local level and revised based on design-based research principles. Subsequently, the LWGs translated their LEs to English. This allowed for sharing their LE with a collaborating LWG (cLWG) in another partner country. The LE was then translated in the cLWG local language and enacted in a different cultural context. The LEs focus on socio-scientific issues and target primary and secondary school students. Five out of seven are presented here: Biotechnology and Climate Change - Cyprus, Nicotine Addiction - Israel, Extraterrestrial Life - Sweden, and Fog control - Greece. They are available in English and in two additional languages each, for widespread use by primary and secondary school educators. Empirical, quantitative and qualitative results on the effectiveness of these five LEs in authentic classrooms are presented.
Keywords: Multilingual learning environments; Participatory design; Primary-secondary students; Socio-scientific topics; Web-based inquiry